READING and FEELING: the effects of a literature-based intervention designed to increase emotional competence in second and third graders - Kumschick, Irina R.; Beck, Luna; Eid, Michael; Witte, Georg; Klann-Delius, Gisela; Heuser, Isabella; Steinlein, Rüdiger; Menninghaus, Winfried (Frontiers in Psychology, 2014)
Emotional competence has an important influence on development in school. We hypothesized that reading and discussing children’s books with emotional content increases children’s emotional competence. To examine this assumption, we developed a literature-based intervention, named READING and FEELING, and tested it on 104 second and third graders in their after-school care center. Children who attended the same care center but did not participate in the emotion-centered literary program formed the control group (N = 104). Our goal was to promote emotional competence and to evaluate the effectiveness of the READING and FEELING program. Emotional competence variables were measured prior to the intervention and nine weeks later, at the end of the program. Results revealed significant improvements in the emotional vocabulary, explicit emotional knowledge, and recognition of masked feelings. Regarding the treatment effect for detecting masked feelings, we found that boys benefited significantly more than girls. These findings underscore the assumption that children’s literature is an appropriate vehicle to support the development of emotional competence in middle childhood.